INTERACTION ANALYSIS OF THE CONSOLE KNIFE SURFACE WITH THE SOIL - V. A. Nikolaiev (Вестник СибАДИ, 2020)
Introduction. In Russia the use of cyclical equipment to remove the top layer of the soil is not feasible. The problem of the roads construction accelerating, improving their quality can be solved by applying a continuous action unit to form a litter layer. The main working bodies of the unit are buckets, including lower knives, right knives and console knives. A console knife contains the edge of the blade, the front face of the blade, the surface and the lower plane. The analysis of the interaction with the ground elements of the continuous action unit console knife is of theoretical and practical interest.The method of research. A consistent impact of many console knives on the ground within the width of the capture unit by the impact of one conventional console knife on the ground at a distance needed to develop one cubic meter of soil is replaced. The interaction forces of the conventional console knife with the ground are called conventional forces. The method of calculating energy costs when introducing a console knife into the ground is presented: to overcome the pressure of the ground on the front face of the console knife, to lift the ground, to vertical acceleration of the soil of the front bevel, to overcome the friction of the ground on the front face and to overcome the friction of the ground on the lower plane of the console knife. The total energy costs of the interaction of the console knife with the ground volume of one cubic meter are obtained by the addition of private energy expenditures.Results. On the basis of the developed method, energy costs are calculated when introducing a console knife into the ground: to overcome the pressure of the ground on the front face of the console knife, to lift the ground, to vertical acceleration of the soil of the front bevel, to overcome the friction of the ground on the front face and to overcome the friction of the ground on the lower plane of the console knife. The total energy costs and their structure when the console knife interacts with the ground volume of one cubic meter are defined. The horizontal longitudinal force needed to move the console knife has been determined.Conclusion. The total energy needed to cut the ground with console knives is about 20 kJ/cub.m. At the same time energy costs for the interaction of console knives blades edges with soil about 7,000 J/cub.m, on the interaction of the packing console knives blades with the ground about 6,000 J/cub.m, to overcome the ground friction on the lower plane of the console knife 7, 000 J/cub.m. To determine the total energy costs of cutting the ground with buckets of the unit to remove the top layer of the soil from the underlying layer of the road, the interaction with the soil of other elements of the bucket is necessary to be analyzed.